2022
DOI: 10.1073/pnas.2200592119
|View full text |Cite
|
Sign up to set email alerts
|

Omicron mutations enhance infectivity and reduce antibody neutralization of SARS-CoV-2 virus-like particles

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant contains extensive sequence changes relative to the earlier-arising B.1, B.1.1, and Delta SARS-CoV-2 variants that have unknown effects on viral infectivity and response to existing vaccines. Using SARS-CoV-2 virus-like particles (VLPs), we examined mutations in all four structural proteins and found that Omicron and Delta showed 4.6-fold higher luciferase delivery overall relative to the ancestral B.1 lineage, a property conferre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 6 publications
(10 reference statements)
7
71
0
Order By: Relevance
“…In line with multiple previous reports (e.g. [23][24][25][26][27][28][29][30][31] ), functional analyses revealed that the Delta sub-lineages (AY.122 and AY.36.1) were more resistant against antibody-mediated neutralization compared to the Alpha variant (B.1.1.7), but much more sensitive in comparison with the Omicron variant (BA.1). The two Delta sub-lineages AY.122 and AY.36.1 had similar neutralization sensitivity, but AY.36.1 showed a clear replication advantage compared to AY.122.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with multiple previous reports (e.g. [23][24][25][26][27][28][29][30][31] ), functional analyses revealed that the Delta sub-lineages (AY.122 and AY.36.1) were more resistant against antibody-mediated neutralization compared to the Alpha variant (B.1.1.7), but much more sensitive in comparison with the Omicron variant (BA.1). The two Delta sub-lineages AY.122 and AY.36.1 had similar neutralization sensitivity, but AY.36.1 showed a clear replication advantage compared to AY.122.…”
Section: Discussionsupporting
confidence: 88%
“…All the Delta sub-lineages were outcompeted by the Omicron variant in the beginning of 2022 34 . As also reported by several other studies 24,25,27,31,35,36 , the robust neutralization evasion by the Omicron variant indicates that the Omicron variant is more adept than the Delta to spread in populations that are vaccinated, which explains the takeover of AY.36.1 by the Omicron variant despite the early Omicron variant BA.1 has no clear replication advantage compared to AY.36.1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, if Omicron infection is less associated with severe COVID-19, it was also shown to be more contagious than Delta infection (Syed et al 2022;Cui et al 2022); this explains why many deaths were still observed during the BA-1 and BA-2 waves, the low frequency of severe form being counterbalanced by the massive number of infections. This observation undermines the statements describing Omicron as a step of SARS-CoV-2 toward a more "banal" coronavirus (Balloux et al 2022;Callaway 2021;Gudina, Ali, et Froeschl 2022), such as 229E, NL63, OC43 and HKU1, and is an argument to maintain high During the second quarter of 2022, new Omicron subvariants, BA.4 and BA.5, progressively became predominant in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Between December 2021 and April 2022, it was responsible for the most massive waves so far of SARS-CoV-2 infection in Europe, North America, China and Japan since the beginning of the pandemic (ECDC 2022). The range of Omicron VOC waves is considered to be related to increased infectivity and to immune escape from neutralising antibodies resulting from previous SARS-CoV-2 infection, vaccination, or both (Syed et al 2022;Cui et al 2022).…”
Section: Introductionmentioning
confidence: 99%